PERANCANGAN MEDIA PROMOSI PRODUK UKM TANGGULANGIN MCH. CHOIRI SEBAGAI UPAYA MENINGKATKAN CITRA PRODUK - Mukin, Ronald Jeremias; Karsam, Karsam; Riqqoh, Abdullah Khoir (Jurnal ArtNouveau, 2014)
The image of a product can measured with the impression and responses to someone. It takes an effort to boost a companyâs image. ukm is the object of peopleâs economy and become the driving force of the national economy. Tanggulangin is the leather industry. mch.choiri ukm industries is one which is in the leather industry in Tanggulangin. Established in 1979 fondend by Mr.H. Mochmmad Choiri. Have a product brand lee choir. Due to the mistake on previous promotional media that too the ukm industry name accentuate rather than brand product belong to the product brand lee choir less stand out. Error in compelling social class also cause segmentation brand is increasingly marginalized. Needed a proper media promotions in order to emphasise the brand product has advantages that lee choir from the quality and elegant design. The existence of the design is expected to improve the image of products of the brand lee choir.